Description of vaccine clinical trials in Africa: a narrative review - Duduzile Ndwandwe; Kopano Dube; Lindi Mathebula; Charles S. Wiysonge (Taylor & Francis Group, 2020)
Clinical research is important in establishing the effects of health-care interventions. Vaccine clinical trials are to examine the effectiveness and safety of vaccines for the prevention of diseases. Africa has a high burden of infectious diseases such as malaria, tuberculosis, HIV/AIDS, and Ebola virus disease. Here we report a database surveillance study of vaccine-related clinical trials conducted in Africa. An objective is to address and profile vaccine clinical trials conducted in Africa. Data were extracted from the WHO International Clinical Trials Registry Platform on 22 July 2018 and updated on 05 September 2019. We found that 61% of the 377 clinical trials were registered prospectively and 35% registered retrospectively. About 72% of the trials were single-country studies and within the country, most trials (86%) were single-center studies. The proportion of trials involving multiple African countries was 11% and that of trials involving countries outside of Africa was 16%. The biggest funder of the vaccine trials (34%) was industry, followed by governments (25%) and universities (21%). The most studied diseases were malaria (20%), HIV/AIDS (15%), tuberculosis (7%), and Ebola virus disease (6%). Most of the vaccine trials were conducted in adults (42%). The trials ranged from phase I to phase IV, with most of the trials being in phase I (18%) and phase III (18%). The conduct of vaccine clinical trials in Africa seeks to address the disease epidemics faced by the continent. There is a need for more investments from governmental bodies toward vaccine research in Africa. Further, African country collaborations are needed in efforts to find African solutions to the current infectious disease threats faced by the continent.